Preparation method and application of artemisia carbon dot modified crystalline carbon nitride material

CN122375598BActive Publication Date: 2026-10-30ANHUI UNIVERSITY OF TRADITIONAL CHINESE MEDICINE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610821449.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-30
Estimated Expiration
2046-06-09

AI Technical Summary

Technical Problem

然而,单一TCDs存在抗菌活性相对较弱、长效稳定性不足等问题

Benefits of technology

改善CCN电荷传输性能,提升抗菌效果。A-CDs嵌入CCN层间后,利用其良好的电子传输能力,可降低CCN的激子结合能、抑制电荷复合。稳态及时间分辨荧光光谱表明,复合材料的荧光强度明显淬灭、荧光寿命缩短,证实了光生电荷分离效率的提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122375598B_ABST
    Figure CN122375598B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of photocatalytic nano antibacterial materials, and discloses a preparation method and application of artemisia carbon dot modified crystalline carbon nitride material. The material is composed of A-CDs and CCN, A-CDs retains the biological activity functional groups of artemisia and is uniformly modified in the interlayer of CCN. The preparation method comprises the following steps: preparing CCN solid and A-CDs powder respectively, then dispersing the two in deionized water, adjusting pH, and then performing ultrasonic dispersion, drying, grinding and staged calcination treatment, so as to obtain A-CDs@CCN material. The application improves the charge separation efficiency by embedding A-CDs in the interlayer of CCN, realizes the synergistic antibacterial effect of A-CDs and CCN, has high inhibition activity on staphylococcus aureus and escherichia coli, and is not easy to induce drug resistance. The preparation process is simple, the raw material cost is low, the obtained material is uniform in composition and stable in structure, and can be used in the field of antibacterial.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalytic nano-antibacterial materials technology, specifically relating to a method for preparing and applying a crystalline carbon nitride material modified with Artemisia argyi carbon dots. Background Technology

[0002] Microbial infections, especially drug resistance caused by opportunistic pathogens such as Staphylococcus aureus and Escherichia coli, have become a major challenge in global public health. The overuse and misuse of traditional antibiotics have accelerated the emergence and spread of multidrug-resistant bacteria. Therefore, developing novel antimicrobial strategies that are broad-spectrum, highly effective, and less likely to induce resistance is an important direction for current research.

[0003] Graphitic carbon nitride (PCN), as a non-metallic photofunctional material, has attracted attention in the antibacterial field due to its suitable band structure, good chemical stability, and biocompatibility. However, conventional PCN suffers from defects such as high photogenerated electron-hole recombination rates and insufficient surface active sites, limiting its antibacterial efficiency. To improve charge separation efficiency, crystalline carbon nitride (CCN), with higher crystallinity and fewer structural defects, has been developed. Nevertheless, the residual exciton binding energy within CCN still leads to partial charge binding, and its single physicochemical properties are insufficient to meet the requirements for efficient synergistic antibacterial action.

[0004] Carbon dots (CDs), as novel zero-dimensional carbon-based materials, possess excellent electron transport capabilities and hold promise for improving the interfacial charge transfer efficiency of composite materials. Among them, traditional Chinese medicine carbon dots (TCDs) prepared using Chinese medicinal herbs as precursors can partially retain characteristic functional groups (such as hydroxyl and carbonyl groups) from the original herbs during carbonization, endowing them with certain inherent antibacterial activities. However, single TCDs suffer from relatively weak antibacterial activity and insufficient long-term stability.

[0005] In summary, CCN is limited by its own charge separation efficiency, while TCDs suffer from insufficient antibacterial strength. Theoretically, combining TCDs and CCN may achieve synergistic effects, but the compatibility of the two in antibacterial systems, methods for regulating interface structure, and the synergistic antibacterial mechanism have not been systematically studied. Therefore, how to effectively load and uniformly disperse TCDs on CCN, and utilize their interaction to optimize the charge behavior of CCN while simultaneously leveraging the inherent antibacterial activity of TCDs, is a pressing technical problem to be solved in this field. Summary of the Invention

[0006] This invention aims to overcome the shortcomings of the prior art and provide a method for preparing and applying a crystalline CCN material modified with Artemisia argyi carbon dots (A-CDs) (A-CDs@CCN). By embedding A-CDs into the interlayer of CCN to regulate exciton dissociation, combined with bioactive functional groups for synergistic antibacterial effects, the resulting material has uniform composition, stable structure, and high antibacterial efficiency.

[0007] An A-CDs@CCN material is formed by stepwise preparation and composite modification of A-CDs and CCN. The A-CDs retain the bioactive functional groups of Artemisia argyi and are uniformly modified in the CCN interlayer. The A-CDs@CCN material is prepared through the following steps: S1, Preparation of CCN material: Urea was ground evenly and then subjected to two heating and holding treatments to obtain solid CCN; Preparation of S2 and A-CDs materials: After processing dried Artemisia argyi leaves, they were mixed with deionized water and sonicated. The mixture was then subjected to heat treatment in a reaction vessel, centrifugation, extraction, filtration, dialysis and drying to obtain A-CDs powder. S3. Preparation of A-CDs@CCN material: The CCN obtained in step S1 and the A-CDs obtained in step S2 are dispersed in deionized water, the pH is adjusted to 5.0~6.0, and then ultrasonicated, stirred and dried. The resulting solid is then ground, heated and kept warm in a tube furnace under nitrogen atmosphere in stages and cooled to obtain A-CDs@CCN material.

[0008] Preferably, the amount of urea used in step S1 is 4-6 g, and the initial heating rate is 4-6 °C / min. -1 The temperature is raised to 540~560℃ and held for 3.5~4.5 h; the second heating rate is 4~6℃·min. -1 The temperature is raised to 490~510℃ and held for 1.5~2.5 hours.

[0009] Preferably, in step S1, after the urea is ground evenly, it is placed in an alumina crucible and then placed in a muffle furnace for the first heating and heat preservation treatment; after the intermediate is ground evenly, it is placed in a muffle furnace again for the second heating and heat preservation treatment.

[0010] Preferably, in step S2, the dried mugwort leaves are processed by grinding them into powder and then passing them through a 100-mesh sieve. The amount of mugwort powder used is 2-4 g, the amount of deionized water used is 15-25 mL, and the ultrasonic time is 15-25 min.

[0011] Preferably, in step S2, the temperature of the reactor is 170~190℃ and the holding time is 9~11 h; after centrifugation, the supernatant is taken and extracted with dichloromethane. After extraction, it is filtered through a 0.22 μm nylon membrane and the dialysis time is 20~28 h. The drying method is vacuum freeze drying and the drying time is 16-24 h.

[0012] Preferably, in step S3, the amount of CCN used is 90-110 mg, the amount of A-CDs used is 1-3 mg, and the amount of deionized water used is 40-60 mL, using 0.1 mol / L... -1 Adjust the pH with dilute hydrochloric acid.

[0013] Preferably, in step S3, the ultrasonic treatment time is 25-35 min, the stirring time is 3-5 h, and the oven drying temperature is 55-65℃.

[0014] Preferably, in step S3, under a nitrogen atmosphere in the tube furnace, the initial heating rate is 2~4℃·min. -1 Heat to 200~250℃ and hold for 0.5~1 h.

[0015] Preferably, in step S3, the second heating rate in the tube furnace is 4~6℃·min. -1 The temperature is raised to 540~560℃, and the holding time is 1.5~2.5 h. The cooling method is natural cooling to room temperature.

[0016] Preferably, the A-CDs@CCN material is used in the field of photocatalytic antibacterial.

[0017] The advantages of this invention compared to the prior art are as follows: Improving the charge transport properties of CCN enhances its antibacterial effect. After A-CDs are embedded in the CCN interlayer, their excellent electron transport capabilities reduce the exciton binding energy of CCN and inhibit charge recombination. Steady-state and time-resolved fluorescence spectroscopy show that the fluorescence intensity of the composite material is significantly quenched and the fluorescence lifetime is shortened, confirming the improved photogenerated charge separation efficiency.

[0018] This study achieves synergistic antibacterial effects of A-CDs and CCN, overcoming the limitations of single materials. A-CDs retain the bioactive functional groups of Artemisia argyi, which can directly disrupt bacterial cell membranes; CCN provides stable support. The synergistic effect of the two results in significantly higher antibacterial rates against Staphylococcus aureus and Escherichia coli than either A-CDs or CCN alone, and they also exhibit excellent clearance capabilities against bacterial biofilms.

[0019] (3) The preparation process is simple and the material structure is stable and uniform. The raw materials are widely available and inexpensive, and no complicated equipment or toxic reagents are required. In the obtained material, A-CDs are uniformly dispersed in the CCN interlayer without obvious agglomeration. The hydrophilicity and specific surface area are better than those of the blank CCN, and it has good application prospects. Attached Figure Description

[0020] Figure 1 The images shown are transmission electron microscope (TEM) images (a), size distribution diagram (b), high resolution transmission electron microscope (HRTEM) images (c), and atomic force microscope (AFM) images (d) of the A-CDs material prepared in Comparative Example 2. Figure 2 The image shows the Fourier Transform Infrared (FT-IR) spectrum of the A-CDs material prepared in Comparative Example 2. Figure 3The image shows a TEM image of the CCN material prepared in Comparative Example 1. Figure 4 These are TEM images of the A-CDs@CCN material prepared in Example 1; Figure 5 The images show the X-ray diffraction (XRD) patterns of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1. Figure 6 These are water contact angle test images of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1; Figure 7 The nitrogen adsorption-desorption curves (BET) of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1 are shown. Figure 8 The FT-IR of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1 are shown. Figure 9 The X-ray photoelectron spectroscopy (XPS) spectra of the A-CDs@CCN material prepared in Example 1, the CCN material prepared in Comparative Example 1, and the A-CDs material prepared in Comparative Example 2 are shown, where (a) is the full spectrum, (b) is the C 1s spectrum, (c) is the N 1s spectrum, and (d) is the O 1s spectrum. Figure 10 The electrochemical impedance spectroscopy (EIS) (a) and transient photocurrent spectrum (b) of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1 are shown. Figure 11 The fluorescence spectra (PL)(a) and time-resolved fluorescence spectra (TR-PL)(b) of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1 are shown. Figure 12 The following are temperature-dependent fluorescence spectra of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1: (a) is the temperature-dependent fluorescence emission spectrum of the CCN material, (b) is the temperature-dependent fluorescence emission spectrum of the A-CDs@CCN material, and (c) is the fitted exciton binding energy of the two materials. Figure 13 The images show a comparison of the anti-Staphylococcus aureus performance of the A-CDs@CCN material prepared in Example 1, the CCN material prepared in Comparative Example 1, and the A-CDs material prepared in Comparative Example 2. In the images, (a) is a colony plate count photograph, (b) is a fluorescence image stained with Calcein-AM / PI, (c) is a biofilm image stained with crystal violet, (d) is the antibacterial rate, and (e) is the biofilm destruction rate.

[0021] Figure 14The images show a comparison of the anti-Escherichia coli performance of the A-CDs@CCN material prepared in Example 1, the CCN material prepared in Comparative Example 1, and the A-CDs material prepared in Comparative Example 2. In the images, (a) is a colony plate count photograph, (b) is a fluorescence image stained with Calcein-AM / PI, (c) is a biofilm image stained with crystal violet, (d) is the antibacterial rate, and (e) is the biofilm destruction rate. Detailed Implementation

[0022] To make the above-mentioned objectives, features, and advantages of the present invention more readily understood, the specific embodiments of the present invention will be described in detail below with reference to examples. The following content is only for illustrative purposes and explanation of the inventive concept. Those skilled in the art can make various modifications, additions, or similar substitutions to the specific embodiments described, as long as they do not deviate from the scope defined by the core concept of the present invention, and all such modifications and additions should be included in the protection scope of the present invention.

[0023] The preparation method of the present invention will be described in detail below through specific embodiments and comparative examples.

[0024] Example 1 A method for preparing A-CDs@CCN material, comprising the following steps: Preparation of S1 and CCN materials: Grind 5 g of urea evenly, place it in an alumina crucible, and put it in a muffle furnace at 5℃·min. -1 The temperature was raised to 550℃ and held for 4 hours to obtain an intermediate; the obtained intermediate was then ground uniformly and then heated again at 5℃·min. -1 The temperature was raised to 500℃ and held for 2 hours to obtain a pale yellow CCN solid. Preparation of S2 and A-CDs materials: Dried Artemisia argyi leaves were ground into powder and passed through a 100-mesh sieve; 3 g of Artemisia argyi powder and 20 mL of deionized water were ultrasonicated for 20 min and then transferred to a reaction vessel and kept at 180℃ for 10 h; after the reaction was completed, the mixture was centrifuged, and the supernatant was extracted with dichloromethane, filtered through a 0.22 μm nylon membrane, dialyzed for 24 h, and then freeze-dried under vacuum for 20 h to obtain deep yellow A-CDs powder; Preparation of S3 and A-CDs@CCN materials: 100 mg of CCN obtained in step S1 and 2 mg of A-CDs were dispersed in 50 mL of deionized water, and then... -1 The pH was adjusted to 5.5 with dilute hydrochloric acid, and the mixture was sonicated for 30 min, stirred for 4 h, and then dried in a 60℃ oven. The resulting solid was ground evenly and placed in a tube furnace. Under a nitrogen atmosphere, it was first dried at 3℃·min. -1 Heat to 220℃ and hold for 0.8 h, then increase the temperature by 5℃·min. -1The temperature was raised to 550℃ and held for 2 hours, then naturally cooled to room temperature to obtain brownish-yellow A-CDs@CCN powder.

[0025] Example 2 A method for preparing A-CDs@CCN material, comprising the following steps: Preparation of S1 and CCN materials: 4 g of urea was ground evenly and placed in an alumina crucible. The crucible was then placed in a muffle furnace at 4℃·min. -1 The temperature was raised to 540℃ and held for 3.5 h to obtain an intermediate; the obtained intermediate was then ground uniformly and subjected to a further heating at 4℃·min. -1 The temperature was raised to 490℃ and held for 1.5 h to obtain a pale yellow CCN solid. Preparation of S2 and A-CDs materials: Dried Artemisia argyi leaves were ground into powder and passed through a 100-mesh sieve; 2 g of Artemisia argyi powder and 15 mL of deionized water were ultrasonicated for 15 min and then transferred to a reaction vessel and kept at 170℃ for 9 h; after the reaction was completed, the mixture was centrifuged, and the supernatant was extracted with dichloromethane, filtered through a 0.22 μm nylon membrane, dialyzed for 20 h, and then freeze-dried under vacuum for 16 h to obtain deep yellow A-CDs powder; Preparation of S3, A-CDs@CCN material: 90 mg of CCN obtained in step S1 and 1 mg of A-CDs were dispersed in 40 mL of deionized water, and then... -1 The pH was adjusted to 5.0 with dilute hydrochloric acid, and the mixture was sonicated for 25 min, stirred for 3 h, and then transferred to a 55℃ oven for drying. The resulting solid was ground evenly and placed in a tube furnace. Under a nitrogen atmosphere, it was first dried at 2℃·min. -1 Heat to 200℃ and hold for 0.5 h, then increase the temperature by 4℃·min. -1 The temperature was raised to 540℃ and held for 1.5 h, then naturally cooled to room temperature to obtain brownish-yellow A-CDs@CCN powder.

[0026] Example 3 A method for preparing A-CDs@CCN material, comprising the following steps: Preparation of S1 and CCN materials: 6 g of urea was ground evenly and placed in an alumina crucible. The crucible was then placed in a muffle furnace and heated to 6℃·min. -1 The temperature was raised to 560℃ and held for 4.5 h to obtain an intermediate; the obtained intermediate was then ground uniformly and subjected to a further heating at 6℃·min. -1 The temperature was raised to 510℃ and held for 2.5 h to obtain a pale yellow CCN solid. Preparation of S2 and A-CDs materials: Dried Artemisia argyi leaves were ground into powder and passed through a 100-mesh sieve; 4 g of Artemisia argyi powder and 25 mL of deionized water were ultrasonicated for 25 min and then transferred to a reaction vessel and kept at 190℃ for 11 h; after the reaction was completed, the mixture was centrifuged, and the supernatant was extracted with dichloromethane, filtered through a 0.22 μm nylon membrane, dialyzed for 28 h, and then freeze-dried under vacuum for 24 h to obtain deep yellow A-CDs powder; Preparation of S3 and A-CDs@CCN materials: 110 mg of CCN obtained in step S1 and 3 mg of A-CDs were dispersed in 60 mL of deionized water, and then dissolved in 0.1 mol L⁻¹ water. -1 The pH was adjusted to 6.0 with dilute hydrochloric acid, and the mixture was sonicated for 35 min, stirred for 5 h, and then dried in a 65℃ oven. The resulting solid was ground evenly and placed in a tube furnace. Under a nitrogen atmosphere, it was first dried at 4℃·min. -1 Heat to 250℃ and hold for 1 hour, then increase the temperature by 6℃·min. -1 The temperature was raised to 560℃ and held for 2.5 h, then naturally cooled to room temperature to obtain brownish-yellow A-CDs@CCN powder.

[0027] Comparative Example 1 (Blank CCN material) A method for preparing CCN material, comprising the following steps: Only CCN was prepared, without combining it with A-CDs, and the steps were the same as step S1 in Example 1.

[0028] Comparative Example 2 (Blank A-CDs material) Only A-CDs were prepared without combining them with CCN, and the steps were the same as step S2 in Example 1.

[0029] Figure 1 The images show TEM (a), size distribution (b), HRTEM (c), and AFM (d) images of the A-CDs material prepared in Comparative Example 2. As can be seen from image (a), the A-CDs are spherical with a particle size of approximately 3.0–7.5 nm (Figure b), a lattice fringe spacing of 0.21 nm (Figure c), and a height of approximately 5.5 nm (Figure d). Figure 2 The FT-IR of the A-CDs material prepared in Comparative Example 2 is shown. The A-CDs at 3378 cm⁻¹... -1 and 2926 cm -1 OH / NH and CH stretching vibration peaks appeared at [location missing]. Additionally, C=O / C=N peaks were observed at 1593 cm⁻¹. -1 C=C (1398 cm) -1 ), CN (1256cm) -1 ) and COC (1031 cm -1The above results indicate that the surface of A-CDs contains abundant functional groups such as hydroxyl and carboxyl groups, which can endow A-CDs with pharmacological activity and are crucial in antibacterial activity.

[0030] Figure 3 This is a TEM image of the CCN material prepared in Comparative Example 1, which shows a typical two-dimensional sheet-like structure.

[0031] Figure 4 The image shows a TEM image of the A-CDs@CCN material prepared in Example 1. The A-CDs are circled in red. As can be seen, the A-CDs are uniformly attached to the CCN surface without agglomeration.

[0032] Figure 5 The images show the XRD patterns of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1. The (002) diffraction peak of A-CDs@CCN is slightly shifted to a lower angle than that of CCN, indicating a slight increase in interlayer spacing, which verifies that A-CDs were successfully embedded in the CCN sheet structure.

[0033] Figure 6 These are images showing the water contact angle test results of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1. The contact angle of CCN is 46.4°, while the contact angle of A-CDs@CCN decreases to 29.1°, indicating that its hydrophilicity is significantly enhanced.

[0034] Figure 7 The BET values ​​are for the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1. Compared with CCN, A-CDs@CCN exhibits a larger specific surface area and a higher concentration of porosity, which helps to generate more active sites and thus enhances photocatalytic antibacterial properties.

[0035] Figure 8 The images show the FT-IR spectra of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1. No A-CDs absorption peak was observed in the FT-IR spectra of A-CDs@CCN, which may be attributed to the limited content of A-CDs and their overlap with the characteristic peak positions of CCN. Notably, both CCN and A-CDs@CCN exhibited absorption peaks in the 3000-3300 cm⁻¹ range. −1 The slight differences in the broad absorption bands may be attributed to the introduction of A-CDs. These results directly confirm that A-CDs, rich in hydrophilic functional groups such as hydroxyl and carboxyl groups, were successfully introduced into the CCN structure, providing a crucial foundation for subsequent antibacterial activity.

[0036] Figure 9The XPS spectra of the A-CDs@CCN material prepared in Example 1, the CCN material prepared in Comparative Example 1, and the A-CDs material prepared in Comparative Example 2 are shown. (a) is the full spectrum, (b) is the C 1s spectrum, (c) is the N 1s spectrum, and (d) is the O 1s spectrum. The XPS full spectra of A-CDs, CCN, and A-CDs@CCN show the presence of C, N, and O elements (Figure a). Specifically, the C 1s peaks of A-CDs at 284.8, 286.1, and 288.5 eV correspond to CC / C=C, CO / CN, and C=O bonds, respectively. CCN shows two characteristic peaks at 284.8 and 288.3 eV, belonging to CC / C=C and NC=N bonds, respectively (Figure b). Notably, compared to CCN, A-CDs@CCN exhibits a new, weak CO / CN peak at 286.1 eV, originating from the oxygen- and nitrogen-containing functional groups of A-CDs. In the N1s spectrum, A-CDs contain pyrrole nitrogen (399.9 eV) and graphitic nitrogen (400.9 eV), corresponding to the characteristic peaks of CN=C, N-(C)3, and NH groups, respectively, in CCN and A-CDs@CCN (Figure c). In Figure (d), the peaks detected at 532.2 and 533.3 eV in A-CDs@CCN are attributed to a mixture of oxygen-containing functional groups (CO / OH) and adsorbed oxygen in A-CDs, while the oxygen elements in CCN all originate from adsorbed oxygen. These results confirm that A-CDs, with their π-conjugated core composed of aromatic rings and nitrogen heterocycles and abundant hydroxyl and carboxyl functional groups on the surface, have been successfully introduced into CCN.

[0037] Figure 10 Figures (a) and (b) show the EIS (Electronic Image Current) spectra of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1. In Figure (a), the impedance arc radius of A-CDs@CCN is significantly smaller than that of CCN, indicating a reduction in charge transfer resistance. In Figure (b), the transient photocurrent spectrum confirms that A-CDs@CCN exhibits a stronger photocurrent response under visible light irradiation. Figures (a) and (b) together demonstrate that A-CDs effectively promote charge separation in the composite material.

[0038] Figure 11 The figures are PL(a) and TR-PL(b) of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1. The fluorescence intensity of A-CDs@CCN was significantly quenched (Figure a), and the average fluorescence lifetime was shortened from 4.5 ns to 3.6 ns (Figure b), confirming that the exciton dissociation process was accelerated and an efficient interfacial charge transfer channel was formed.

[0039] Figure 12Temperature-dependent fluorescence spectra of the A-CDs@CCN material prepared in Example 1 and the CCN material prepared in Comparative Example 1 are shown. (a) shows the temperature-dependent fluorescence emission spectrum of the CCN material, (b) shows the temperature-dependent fluorescence emission spectrum of the A-CDs@CCN material, and (c) shows the fitted exciton binding energy of the two materials. As shown in (a) and (b), the fluorescence intensity of both CCN and A-CDs@CCN gradually decreases with increasing temperature, consistent with exciton thermal delocalization behavior. The exciton binding energy (E) of CCN is obtained by fitting the fluorescence intensity versus temperature curve. b The value is 52.58 meV, while the E of A-CDs@CCN is... b The voltage dropped to 41.46 meV, a reduction of 21.7% (Figure c). This result directly confirms that the introduction of A-CDs significantly weakens the exciton binding of CCN, thereby increasing the generation of free charges from a thermodynamic source.

[0040] Figure 13This is a comparison of the anti-Staphylococcus aureus performance of the A-CDs@CCN material prepared in Example 1, the CCN material prepared in Comparative Example 1, and the A-CDs material prepared in Comparative Example 2. (a) is a colony plate count photograph; (b) is a fluorescence image stained with Calcein-AM / PI; (c) is a biofilm image stained with crystal violet; (d) is the antibacterial rate; and (e) is the biofilm disruption rate. Staphylococcus aureus was used as a model bacterium to evaluate the antibacterial performance of the prepared samples. As shown in Figure (d), after 2.5 h of visible light irradiation, the sterilization effect of A-CDs against Staphylococcus aureus reached 87.76%, fully demonstrating that A-CDs retained some of the antibacterial pharmacological activity of Artemisia argyi. CCN showed a moderate antibacterial effect against Staphylococcus aureus. Notably, the antibacterial rate of A-CDs@CCN against Staphylococcus aureus was as high as 99.06%, significantly better than A-CDs and CCN. The above antibacterial experimental results indicate that after CCN introduces A-CDs, it promotes the directional movement of charges by regulating the exciton binding energy, thereby generating more antibacterial active species. Simultaneously, the bioactive A-CDs play a crucial role, ultimately achieving a synergistic effect of photocatalytic oxidation and chemobiological intervention as a dual antibacterial mechanism. Bacterial mortality was further evaluated using a live / dead bacteria staining experiment. As shown in Figure (b), most bacteria in the control group exhibited green fluorescence, indicating that the cell walls remained intact and the bacteria were alive. In the A-CDs and CCN groups, only localized red fluorescence was observed. However, after A-CDs@CCN treatment, bright red fluorescence appeared, indicating that the bacteria were essentially dead, consistent with the colony plate counting results (Figure a). The ability of the samples to disrupt Staphylococcus aureus biofilms was investigated using crystal violet staining (Figures c and e). After treatment with A-CDs@CCN, the staining intensity significantly decreased, and the biofilm removal capacity reached 81.35%, significantly higher than that of the single component (Figure e). These results further demonstrate that A-CDs@CCN not only exhibits higher bactericidal properties under visible light irradiation but also demonstrates excellent bacterial membrane disruption performance. The control group received no additional ingredients.

[0041] The antibacterial activity was determined as follows: The antibacterial properties of the prepared material were evaluated using the plate count method. Before the experiment, all glass containers and reagents were sterilized in an autoclave at 121°C for 20 min. The inactivation experiment was conducted in 10 mL sterile beakers. Staphylococcus aureus and Escherichia coli (3 × 10⁻⁶) were used. 7 Up to 3 × 10 8 CFU mL -1 ) and CCN, A-CDs, and A-CDs@CCN were evenly dispersed in physiological saline (1 mg / mL) -1 Finally, irradiation was performed using a 300 W xenon lamp (λ > 420 nm, 80 mW cm⁻¹). -2The antibacterial effect was evaluated. 100 μL of bacterial suspension was periodically diluted serially to a specific concentration, spread onto agar plates, and incubated at 37 °C for 16 h. A control experiment was conducted under the same conditions without a photocatalyst. All antibacterial experiments were performed in triplicate. The antibacterial rate was calculated using the colony count (N) on the plates, calculated according to formula (1):

[0042] In addition, bacterial suspensions treated with different methods were fixed with formaldehyde and incubated overnight at 4 °C, then dehydrated sequentially with 30%, 50%, 70%, 90%, and 100% ethanol for 15 min each. After drying and metal sputtering, bacterial morphology was observed using a scanning electron microscope. In the live / dead double staining experiment, bacteria treated with different methods were centrifuged and washed with sterile phosphate-buffered saline (PBS). Subsequently, they were stained with Calcein-AM and PI in the dark for 30 min, and then placed in a high-speed, high-resolution tissue cell panoramic scanning imaging workstation for fluorescence imaging.

[0043] The anti-biofilm assay was performed as follows: Bacteria (OD600 = 1) were inoculated into 6-well plates (200 μL per well), and 200 μL of 1% glucose solution and 2 mL of culture medium were added. After culturing for 72 h, the resulting biofilms were treated with different materials. To evaluate the anti-biofilm activity of the materials, the efficiency of biofilm removal was quantified using crystal violet staining. Specifically, the biofilm was fixed with 200 μL of methanol for 15 min and washed with PBS buffer. It was then stained with 100 μL of crystal violet solution (1.0 wt%) for 30 min and rinsed with PBS to remove unbound dye. Subsequently, the stained biofilm was treated with 200 μL of acetic acid (33.3%) for 30 min to dissolve the crystal violet dye. Finally, the absorbance of the samples was measured at 570 nm using a microplate reader to quantify the biofilm biomass.

[0044] Figure 14Figure (d) shows a comparison of the antibacterial performance of the A-CDs@CCN material prepared in Example 1, the CCN material prepared in Comparative Example 1, and the A-CDs material prepared in Comparative Example 2 against *E. coli*. (a) is a colony plate count photograph; (b) is a fluorescence image stained with Calcein-AM / PI; (c) is a biofilm image stained with crystal violet; (d) is the antibacterial rate; and (e) is the biofilm destruction rate. As shown in Figure (d), after 2.5 h of visible light irradiation, the sterilization effect of A-CDs against *E. coli* was 27.06%, fully demonstrating that A-CDs retained some of the antibacterial pharmacological activity of *Artemisia argyi*. CCN showed a moderate antibacterial effect against *E. coli*. The antibacterial rate of A-CDs@CCN against *E. coli* was as high as 94.97%, significantly better than that of A-CDs and CCN. The above antibacterial experimental results indicate that after CCN is introduced into A-CDs, it promotes the directional movement of charges and generates more antibacterial active species by regulating the exciton binding energy. Simultaneously, the bioactive A-CDs play a crucial role, ultimately achieving a synergistic effect of photocatalytic oxidation and chemibiological intervention in the dual antibacterial mechanism. Bacterial mortality was further assessed using a live / dead bacterial staining experiment. As shown in Figure (b), most bacteria in the control group exhibited green fluorescence, indicating that their cell walls remained intact and they were alive. In the A-CDs and CCN groups, only localized red fluorescence was observed. However, after A-CDs@CCN treatment, bright red fluorescence appeared, indicating that the bacteria were essentially dead, consistent with the colony plate counting results (Figure a). Finally, the ability of the samples to disrupt the *E. coli* biofilm was investigated using crystal violet staining (Figures c and e). After treatment with A-CDs@CCN, the staining intensity was significantly lighter, and the biofilm removal capacity reached 68.84%, significantly higher than that of the single component (Figure e). These results further demonstrate that A-CDs@CCN not only exhibits higher bactericidal properties under visible light irradiation but also demonstrates excellent bacterial membrane disruption performance. The control group consisted of no added materials.

Claims

1. A method for preparing A-CDs@CCN material, characterized in that, Includes the following steps: S1, Preparation of CCN material: Urea was ground evenly and then subjected to two heating and holding treatments to obtain solid CCN; Preparation of S2 and A-CDs materials: After processing dried Artemisia argyi leaves, they were mixed with deionized water and sonicated. The mixture was then subjected to heat treatment in a reaction vessel, centrifugation, extraction, filtration, dialysis and drying to obtain A-CDs powder. Preparation of S3 and A-CDs@CCN materials: The CCN obtained in step S1 and the A-CDs obtained in step S2 were dispersed in deionized water, and the pH was adjusted to 5.0~6.

0. After ultrasonication, stirring, and drying, the resulting solid was ground, and then subjected to staged heating and holding in a tube furnace under a nitrogen atmosphere, followed by cooling. The initial heating rate was 2~4℃·min. -1 The temperature is raised to 200~250℃ and held for 0.5~1 h; the secondary heating rate is 4~6℃·min. -1 The temperature was raised to 540~560℃ and held for 1.5~2.5 h, and then naturally cooled to room temperature to obtain A-CDs@CCN material; The A-CDs@CCN material mentioned in step S3 has A-CDs retaining the bioactive functional groups of Artemisia argyi and uniformly dispersed in the CCN layers.

2. The preparation method according to claim 1, characterized in that, In step S1, the amount of urea used is 4-6 g, and the initial heating rate is 4-6 °C·min. -1 The temperature is raised to 540~560℃ and held for 3.5~4.5 h; the second heating rate is 4~6℃·min. -1 The temperature is raised to 490~510℃ and held for 1.5~2.5 hours.

3. The preparation method according to claim 1, characterized in that, In step S1, after the urea is ground evenly, it is placed in an alumina crucible and then placed in a muffle furnace for the first heating and holding treatment; after the intermediate is ground evenly, it is placed in a muffle furnace again for the second heating and holding treatment.

4. The preparation method according to claim 1, characterized in that, In step S2, the dried mugwort leaves are processed by grinding them into powder and then passing them through a 100-mesh sieve. The amount of mugwort powder used is 2-4 g, the amount of deionized water used is 15-25 mL, and the ultrasonic time is 15-25 min.

5. The preparation method according to claim 1, characterized in that, In step S2, the temperature of the reactor is kept at 170~190℃ for 9~11 h. After centrifugation, the supernatant is taken and extracted with dichloromethane. After extraction, it is filtered through a 0.22 μm nylon membrane and dialyzed for 20~28 h. The drying method is vacuum freeze drying for 16~24 h.

6. The preparation method according to claim 1, characterized in that, In step S3, the amount of CCN used is 90-110 mg, the amount of A-CDs is 1-3 mg, and the amount of deionized water is 40-60 mL, using 0.1 mol / L... -1 Adjust the pH with dilute hydrochloric acid.

7. The preparation method according to claim 1, characterized in that, In step S3, the ultrasonic treatment time is 25~35 min, the stirring time is 3~5 h, and the oven drying temperature is 55~65℃.

8. The application of an A-CDs@CCN material prepared by the method according to any one of claims 1-7 in the preparation of antibacterial materials.

Citation Information

Patent Citations

  • Preparation method and application of carbon nanodots with efficient antibacterial properties

    CN111803631A

  • Carbon quantum dot modified graphite carbon nitride composite material as well as preparation method and application thereof

    CN118491554A